2021
DOI: 10.3390/genes12060882
|View full text |Cite
|
Sign up to set email alerts
|

Rice (Oryza sativa) TIR1 and 5′adamantyl-IAA Significantly Improve the Auxin-Inducible Degron System in Schizosaccharomyces pombe

Abstract: The auxin-inducible degron (AID) system is a powerful tool to induce targeted degradation of proteins in eukaryotic model organisms. The efficiency of the existing Schizosaccharomyces pombe AID system is limited due to the fusion of the F-box protein TIR1 protein to the SCF component, Skp1 (Skp1-TIR1). Here, we report an improved AID system for S. pombe that uses the TIR1 from Oryza sativa (OsTIR1) not fused to Skp1. Furthermore, we demonstrate that degradation efficiency can be improved by pairing an OsTIR1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…We showed in this study that, when paired with OsTIR1-F74A, 5-adamantyl-IAA is a highly effective inducer for the AID system and can minimize side effects on the transcriptome. Several recently published studies have also demonstrated that a bulky auxin analog, when paired with a mutant form of OsTIR1 with an enlarged auxin-binding pocket, acts as an effective AID inducer at much lower concentrations than auxin ( Nishimura et al 2020 ; Yesbolatova et al 2020 ; Watson et al 2021 ). When we initiated this study in 2018, 5-adamantyl-IAA was not commercially available and therefore we obtained it by chemical synthesis.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…We showed in this study that, when paired with OsTIR1-F74A, 5-adamantyl-IAA is a highly effective inducer for the AID system and can minimize side effects on the transcriptome. Several recently published studies have also demonstrated that a bulky auxin analog, when paired with a mutant form of OsTIR1 with an enlarged auxin-binding pocket, acts as an effective AID inducer at much lower concentrations than auxin ( Nishimura et al 2020 ; Yesbolatova et al 2020 ; Watson et al 2021 ). When we initiated this study in 2018, 5-adamantyl-IAA was not commercially available and therefore we obtained it by chemical synthesis.…”
Section: Discussionmentioning
confidence: 98%
“…During the preparation of our manuscript, another study on improving the AID system for S. pombe was published ( Watson et al 2021 ). Similar to our findings, Watson et al also showed that OsTIR1 not fused with Skp1 can be expressed from a strong promoter without causing toxicity and is more effective in inactivating mcm4 than the Padh15-skp1-AtTIR1-NLS cassette of the Kanke system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Auxin-induced degradation of Wsc1 in a wsc2 Δ wsc3 Δ mutant strain resulted in severe growth defects when applying OsTIR1 and AID2, whereas Wsc1 was degraded rapidly and efficiently under all conditions tested ( Figure 3 ). The biggest advantage of AID2 clearly is the reduced basal degradation of the target protein ( Watson et al., 2021 ; Yesbolatova et al., 2020 ). Although basal degradation of Wsc1 was fully absent when applying AID2 ( Figure 3 D), the growth phenotype observed for auxin-induced degradation of Wsc1 in a wsc2-3 Δ double delete strain was similar for AID (using 1-NAA and IAA) and AID2 (using 5-Ph-IAA).…”
Section: Discussionmentioning
confidence: 99%
“…4b), suggesting synthetic growth defects of the srr1∆ rad52∆ double deletion. To confirm this, we depleted Rad52 in srr1∆ cells using the auxininduced degron 2 (AID2) system 43 . In the presence of the F-box protein OsTIR1 F74A , an auxin analog 5'-adamantyl-IAA (5'a-IAA) induces polyubiquitin-dependent degradation of the AIDtagged Rad52 protein, Rad52-AID.…”
Section: Srr1 and Rad52 Have Both Overlapping And Non-overlapping Rol...mentioning
confidence: 98%